2006
DOI: 10.1074/jbc.m600744200
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Dissemination of Peroxidative Stress

Abstract: Sterol carrier protein-2 (SCP-2) plays a crucial role in the trafficking and metabolism of cholesterol and other lipids in mammalian cells. Lipid hydroperoxides generated under oxidative stress conditions are relatively long-lived intermediates that damage cell membranes and play an important role in redox signaling. We hypothesized that SCP-2-facilitated translocation of lipid hydroperoxides in oxidatively stressed cells might enhance cytolethality if highly sensitive sites are targeted and detoxification cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Using unilamellar liposomes as [ 14 C]7α-OOH donors and isolated liver mitochondria as acceptors, we found that SCP-2 accelerated peroxide uptake and that this stimulated both chain peroxidation and loss of mitochondrial membrane potential [38]. Subsequent work showed that a transfect clone of hepatoma cells expressing ~10-fold more SCP-2 than a vector control was much more sensitive to 7α-OOH-induced mitochondrial damage and lethality than the control [39,40]. 7α-OH (an SCP-2 ligand, but redox-inactive) and tert -butyl hydroperoxide (redox-active, but not a ligand) showed no such effects.…”
Section: Cholesterol Hydroperoxide Translocation and Traffickingmentioning
confidence: 99%
“…Using unilamellar liposomes as [ 14 C]7α-OOH donors and isolated liver mitochondria as acceptors, we found that SCP-2 accelerated peroxide uptake and that this stimulated both chain peroxidation and loss of mitochondrial membrane potential [38]. Subsequent work showed that a transfect clone of hepatoma cells expressing ~10-fold more SCP-2 than a vector control was much more sensitive to 7α-OOH-induced mitochondrial damage and lethality than the control [39,40]. 7α-OH (an SCP-2 ligand, but redox-inactive) and tert -butyl hydroperoxide (redox-active, but not a ligand) showed no such effects.…”
Section: Cholesterol Hydroperoxide Translocation and Traffickingmentioning
confidence: 99%
“…As we know, inhibition of SCP2 increases cell viability in GPX4 -/fibroblasts or RSL3-treated breast cancer cells, but the mechanism driving this remains obscure [24,25,27]. Since SCP2 is a carrier protein that can carry a variety of lipids (including lipid hydroperoxides), the elevation of SCP2 was likely related to the transport of LPO in OA chondrocytes [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is beyond the scope of this study to examine the various other physiological functions attributed to SCP2, it is noteworthy that cells overexpressing SCP2 become more susceptible to damage/toxicity by 7␣-OOH, a free radical generated by cholesterol hydroperoxides, because cellular SCP2 binds and traffics 7␣-OOH to mitochondria, where it exerts cellular toxicity (25). Whether reduction in SCP2-mediated cytotoxicity underlies the observed reduction in plaque necrosis remains to be established.…”
Section: Scp2 Deficiency Is Atheroprotectivementioning
confidence: 99%